The Role of Siangkaran Cultural Values on Work-Life Balance and Performance: A Qualitative Study of Female Weavers at the Unnoni Tenun MSME in North Toraja - Tangkeallo, Dian Intan; Pongtuluran, Althon K.; Lioso, Fredrick Oktavianus (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study aims to examine how the cultural value of siangkaran in the Toraja community plays a role in creating work-life balance and influencing the performance of female weavers in the Unnoni community, North Toraja. Siangkaran, as a cultural value emphasizing mutual assistance in work, has become a social practice embedded in the daily lives of the weavers. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with 22 participants who are members of the Unnoni weaving group, participatory observation, and documentation of weaving activities. The results indicate that the value of siangkaran allows for a fair distribution of workload, creates a sense of togetherness, and helps the weavers maintain a balance between domestic responsibilities and productive work. Furthermore, siangkaran contributes to improving collective performance, both in terms of timely completion of orders and the quality of the woven products. This study confirms that local cultural values can serve as effective social mechanisms to support the work well-being of women in the informal sector and promote the sustainability of community-based enterprises.